2015
DOI: 10.1039/c5ob00167f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chitin and chitosan stereoisomers by thermostable α-glucan phosphorylase-catalyzed enzymatic polymerization of α-d-glucosamine 1-phosphate

Abstract: The relationship between two aminopolysaccharide stereoisomers, namely α-(1→4)- and β-(1→4)-linked (N-acetyl)-D-glucosamine polymers, is of significant interest within the field of polysaccharide science, as they correspond to amino analogs of the representative abundant natural polysaccharides, viz. amylose and cellulose. While the latter glucosamine polymer is the basis of well-known natural polysaccharides, chitin and chitosan (linear polysaccharides composed of β-(1→4)-linked N-acetyl-D-glucosamine and D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Unnatural donor substrate glucosamine 1‐phosphate (GlcN1P), which has been used with α‐1,4‐glucan phosphorylase to synthesis α‐linked chitosan analogues, was also investigated in reactions with CDP and Pro_7066. It appeared to be an excellent donor for glycosylation with both enzymes, producing trisaccharide 17 in CDP‐catalysed reaction with 4 and trisaccharide 24 in Pro_7066‐catalysed reaction with 1 in 88 and 74 % yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Unnatural donor substrate glucosamine 1‐phosphate (GlcN1P), which has been used with α‐1,4‐glucan phosphorylase to synthesis α‐linked chitosan analogues, was also investigated in reactions with CDP and Pro_7066. It appeared to be an excellent donor for glycosylation with both enzymes, producing trisaccharide 17 in CDP‐catalysed reaction with 4 and trisaccharide 24 in Pro_7066‐catalysed reaction with 1 in 88 and 74 % yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the present investigation, we synthesized the substrate, α (1→4)‐GlcN n , by thermostable phosphorylase‐catalyzed enzymatic polymerization of GlcN‐1‐P from Glc 3 primer (30:1) at 40 °C for 7 days in ammonia buffer containing the Mg 2+ ion [Figure (a)] . The 1 H‐NMR spectrum of the isolated product (D 2 O + acetic acid‐ d 4 ) supported the structure of α (1→4)‐GlcN n with the M n value of 3850 [degree of polymerization = ∼23, Figure (a)].…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] For example, we have found that phosphorylase isolated from thermophilic bacteria (thermostable phosphorylase from Aquifex aeolicus VF5) catalyzes consecutive transfer reactions of D-glucosamine (GlcN) residues from an a-D-glucosamine 1-phosphate (GlcN-1-P) substrate to the nonreducing elongating end of maltotriose (Glc 3 ) primer in acetate buffer to produce a(1!4)-linked oligo-GlcN chains. 30 Furthermore, based on the fact that Pi forms insoluble ammonium magnesium phosphate, 31 the transfer reaction is promoted in ammonia buffer containing Mg 21 ions to promote polymerization while removing Pi as the phosphate precipitate, giving rise to a(1!4)linked amylose analog aminopolysaccharide (a(1!4)-GlcN n ), which corresponds to a stereoisomer of chitosan, b(1!4)-linked GlcN polymer [ Figure 1(a)]. 30,32 In spite of the a(1!4)-linked conformation, a(1!4)-GlcN n does not form a double helix assembly, unlike amylose.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies involved a glycosyltransferase, 10,40 a glycosidephosphorylase, [12][13][14][15] or transglycosidases, 22,41 and produced either statistical copolymers or co-oligomers (of a total size of less than 30 glycosyl units) rather than block copolymers. Here, we demonstrated that the selected glucansucrases (DSR-M and ASR) transfer α-glucosyl residues to acceptor polymers (i) with a conformation and linkage composition different from that of their natural acceptors, and (ii) a size of up to 30 glucosyl residues, producing copolymers comprising up to 171 residues.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same principle, another type of glycan-synthesizing enzyme, α(1 → 4) glucan phosphorylase (SP, EC 2.4.1.1) from Aquifex aeolicus VF5, belonging to the GT35 family of carbohydrate active enzymes (CAZy 11 ), was tested for the in vitro enzymatic synthesis of hybrid polysaccharides. [12][13][14][15] The substrate promiscuity of this enzyme towards glycosyl donors (α-D-Glc-1-phosphate, α-DGlcNAc-1-phosphate and α-D-Man-1-phosphate) was exploited to produce non-natural polysaccharides such as hetero-mannosides and aminopolysaccharides. [13][14][15] The three sugar-phosphate donors were used in the presence of a maltotriose acceptor to obtain different copolymers with maltotriose at the reducing end, on which were grafted α(1 → 4)-mannan, α(1 → 4)-linked glucosaminoglucans or heteromannans (composed of either Glc and GlcNAc units, or Glc and Man units).…”
Section: Introductionmentioning
confidence: 99%